OPTIMALISASI KOMODITAS KACANG TANAH MENJADI PRODUK OLAHAN PANGAN UNGGULAN DI DESA CIKEBEL ATAS CILEGON BANTEN - Suhendi, Endang; Barleany, Dhena Ria; Lestari, Retno Sulistyo; Sari, Denni Kartika; Adiwibowo, Muhammad Triyogo; Kustiningsih, Indar; Ernayati, Widya; Rochmat, Agus (Jurnal Pengabdian Dinamika, 2019)
Cikebel Atas is one of the villages in the Cilegon area, Banten, which is located in a rural area andfar from urban influences. In this village the level of education of the people is very low, and dailylivelihoods are as laborers or motorcycle taxi drivers. Actually this village has the potential forabundant agricultural products, namely in the form of peanuts. Due to lack of knowledge, villagersusually sell these peanuts to collectors at low prices. Peanuts can actually be processed into superiorprocessed products that are characteristic of the region, namely peanut tempeh, peyek, or otherproducts that have higher economic value. The community service program is conducted to providemotivation and knowledge to the community about entrepreneurship, especially in terms of localcommodity management in the form of peanuts. The method is arranged in several concrete steps,namely in the form of counseling or outreach, as well as direct training and practice for peanuttempeh and peyek processing technology. Through these concrete programs, it is targeted that therewill be a change in people's lives in the village of Cikebel Atas, Cilegon, Banten, for the better.